Is Obstructive Sleep Apnea Associated with Higher Covid-19 Severity? - Zacarias, Laíla Cândida; Torres, Danielle Mesquita; Magalhães, Samir Câmara; Sobreira-Neto, Manoel Alves; Leite, Camila Ferreira (Sleep Science, 2024)
Objective To investigate the associations between obstructive sleep apnea (OSA) and coronavirus disease 2019 (COVID-19) severity.Methods Twelve individuals hospitalized in a Brazilian tertiary hospital diagnosed with COVID-19 by reverse transcriptase-polymerase chain reaction (RT-PCR) underwent respiratory polygraphy.Results Polygraphic records identified seven participants without obstructive sleep apnea (OSA) (OSA-) and five with OSA (OSA + ). The OSA+ group presented worse peripheral oxygen saturation (77.6% ± 7.89%) than the OSA- group (84.4% ± 2.57%) (p = 0.041). Additionally, the OSA+ group showed greater COVID-19 severity (100%) than the OSA- group (28.57%) (p = 0.013) and required longer oxygen therapy (p = 0.038), but without difference in the length of hospitalization. The OSA+ group also presented higher rates of platelets (p = 0.008) and D-dimer (1,443 ± 897) than the OSA- group (648 ± 263 ng/mL) (p = 0.019).Conclusion Obstructive sleep apnea in individuals hospitalized due to COVID-19 was associated with higher COVID-19 severity, worse peripheral oxygen saturation, longer oxygen therapy time, and higher platelet and D-dimer rates.
Keywords: COVID-19; obstructive sleep apnea; sleep; polygraphy